PELATIHAN ANBUSO, ZIPGRADE, DAN GOOGLE FORM SEBAGAI ALTERNATIF PENILAIAN PEMBELAJARAN DI ERA DIGITAL - Yuwono, Muhammad Ridlo; Aribowo, Eric Kunto; Indrayanto, Bayu; Firmansah, Fery (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this dedication activity is to provide training so that teachers can use the Anbuso, ZipGrade, and Google Forms applications to carry out learning assessments in the 2013 curriculum. This training held in collaboration with the District Nahdlatul Ulama (Pergunu) Teachers Association in Klaten and Widya Dharma University. The trainees were teachers from the Klaten Pergunu members from MI, MtS, and MA levels, with a large number of participants being 56. The training was held face-to-face on 28-29 August 2019 at MA Al Manshur and held online on 7, 14, 21 September 2019. The results are AnBuso, ZipGrade, and Google Forms applications are practical, simple, fast. Secure applications to apply for learning assessment in the digital age.